An Implementation of the Policy on New Parking Zone Expansion and Its Impact on Increasing Local Own Source Revenue (PAD) in Payakumbuh City : Case Study at the Department of Transportation, Payakumbuh City - Rifnaldi Rifnaldi; Asep Ajidin (Brilliant International Journal Of Management And Tourism, 2026)
Locally Generated Revenue (PAD) is a key indicator of regional economic performance and fiscal capacity in implementing decentralization. To strengthen regional finances, the central government enacted Law Number 1 of 2022, replacing Law Number 34 of 2000 on Regional Taxes and Levies. In response, the Payakumbuh City Government has sought to optimize PAD through the parking levy sector managed by the Transportation Agency. Roadside parking fees are positioned as a strategic revenue source; however, revenue targets have not been achieved optimally. To address this issue, the Mayor of Payakumbuh issued Decree Number 500.11.33/23.3.80/WK-PYK/2025 concerning the Determination of Parking Locations on Public Roads, establishing two new parking areas effective February 12, 2025. This study evaluates the implementation of the parking area expansion policy and analyzes its potential contribution to increasing PAD. The findings reveal that although the policy has been formally implemented, several challenges persist, including weak parking management systems, limited technological utilization, inadequate operational procedures, and insufficient field supervision. Furthermore, low public awareness regarding the importance of parking tickets and reporting violations constrains revenue optimization. Therefore, improvements are required in management systems, human resource capacity, technological integration, supervision mechanisms, and public education to foster orderly parking practices. These measures are expected to enhance the effectiveness of parking levy collection and contribute significantly to increasing PAD in Payakumbuh City.